Longer wings for faster springs – wing length relates to spring phenology in a long‐distance migrant across its range. Issue 1 (8th December 2015) - Hahn, Steffen; Korner‐Nievergelt, Fränzi; Emmenegger, Tamara; Amrhein, Valentin; Csörgő, Tibor; Gursoy, Arzu; Ilieva, Mihaela; Kverek, Pavel; Pérez‐Tris, Javier; Pirrello, Simone; Zehtindjiev, Pavel; Salewski, Volker
Abstract: In migratory birds, morphological adaptations for efficient migratory flight often oppose morphological adaptations for efficient behavior during resident periods. This includes adaptations in wing shape for either flying long distances or foraging in the vegetation and in climate‐driven variation of body size. In addition, the timing of migratory flights and particularly the timely arrival at local breeding sites is crucial because fitness prospects depend on site‐specific phenology. Thus, adaptations for efficient long‐distance flights might be also related to conditions at destination areas. For an obligatory long‐distance migrant, the common nightingale, we verified that wing length as the aerodynamically important trait, but not structural body size increased from the western to the eastern parts of the species range. In contrast with expectation from aerodynamic theory, however, wing length did not increase with increasing migration distances. Instead, wing length was associated with the phenology at breeding destinations, namely the speed of local spring green‐up. We argue that longer wings are beneficial for adjusting migration speed to local conditions for birds breeding in habitats with fast spring green‐up and thus short optimal arrival periods. We suggest that the speed of spring green‐up at breeding sites is a fundamental variable determining the timing of migration that fine tune phenotypes in migrants across their range. Abstract : Wing length as the aerodynamically important trait but not body size increased from western to eastern populations of an obligatory long distance migrant. The directional change in morphometry was not related to migratory distance but to the speed of spring green‐up at breeding sites. We suggest that the speed of spring green‐up at breeding sites is a fundamental variable determining the timing of migration and that environmental heterogeneity at destination may fine tune bird phenotypes across their range.